Penataan Lingkungan Permukiman Berbasis Komunitas di Desa Jomblang Dan Tegalrejo, Dukuh, Sukoharjo dengan pendekatan Green Architecture - Prastowo, Umar; , Ir. Nurhasan, MT (2017)
Environment Community-Based Settlement Arrangement (PLPBK) is an activity that gives an opportunity to the public to not only alleviate poverty in a more comprehensive and integrated approach, but also provide opportunities for people to reorganize their living environment and structuring back their social and economic order. Based Guidelines for Conduct issued by the Directorate General of Human Settlements Ministry of Public Works. Program PLPBK (Environmental Restructuring Community-Based Settlement) is a community activity to plan and build the order of life of citizens by visions of the future are built together, to realize the physical environment that is healthy, orderly, harmonious and sustainable, which is a form of advanced culture community (Community Based Neighborhood Development). Environmental Restructuring Program Community-Based Settlement (Neighborhood Development) is basically a form of stimulant for the success of the community in the village of Hamlet that has been able to build such public institutions; Community Self-Reliance Agency (BKM) in achieving qualification "Helpless BKM towards Self" or BKM Mandiri and has implemented a partnership with the local government or other parties dengaan (channeling). Environmental Restructuring activities Community-Based Settlement in substance is the 5 implementation of the concept of partnership and "channeling" program on a smaller scale, the scale of the Village. Hopefully, through this activity lasts learning process, structuring and institutionalizing the partnership synergy between the community, village governments and local care group. The process is more emphasis on self-reliance, self-reliance and hard work to mobilize all potential resources shared and access a variety of resources from other outside in an effort to develop neighborhoods healthy, orderly, aligned, berjatidiri and sustainably towards the ideals of a prosperous society. Keywords: Environmental Settlement; Jomblang village and Tegalrejo, Hamlet, Sukoharjo; Green Architecture.